2001
DOI: 10.1046/j.1365-2265.2001.01154.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension is a major risk factor for aortic root dilatation in women with Turner's syndrome

Abstract: Women with Turner's syndrome (TS) have a threefold increase in mortality, primarily as a result of their cardiovascular complications. Recently, the risk of fatal aortic dissection has come to light as a major cause of mortality in women with TS. The aim of this study was to assess the prevalence of aortic root dilatation in a group of women with TS and to investigate the factors contributing to its development. Thirty-eight women with TS attending a dedicated adult Turner clinic were examined clinically and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(109 citation statements)
references
References 40 publications
5
101
1
1
Order By: Relevance
“…Aortic root dilatation does not appear to be related to atherosclerosis and is more likely to be due to a mesenchymal defect caused by genetic disorder [32,35]. The most common histological finding of the dilated aorta is elastic fibber fragmentation and cystic medial degeneration [10,21,30,31,38].…”
Section: Prace Poglądowementioning
confidence: 99%
See 1 more Smart Citation
“…Aortic root dilatation does not appear to be related to atherosclerosis and is more likely to be due to a mesenchymal defect caused by genetic disorder [32,35]. The most common histological finding of the dilated aorta is elastic fibber fragmentation and cystic medial degeneration [10,21,30,31,38].…”
Section: Prace Poglądowementioning
confidence: 99%
“…However, aortic root dilatation may occur in the absence of risk factors in approximately 5% of females with TS, indicating that all females with TS should be monitored for aortic root dilatation [32,34,35,40].…”
Section: Prace Poglądowementioning
confidence: 99%
“…The concept of chromosomal imbalance, and thus disturbed pairing during mitosis, has also been implicated (320). An increase in aortic root diameter, which is a risk factor for developing aortic dilatation and later rupture, is often seen and probably depends on blood pressure (321). However, prospective studies are needed in order to study how the risk of aortic dissection can be reduced.…”
Section: Congenital Malformations Of the Heartmentioning
confidence: 99%
“…How should a person with 5% (or less) 45,X cells and 95% 46,XX cells be considered, knowing that normally a karyotype is performed on Table 1 Detailed list of abnormalities associated with Turner syndrome with the tentative frequency of a specific abnormality given as a percentage. The table is compiled from different sources (8,55,178,296,305,307,321,350).…”
Section: Introductionmentioning
confidence: 99%
“…Review of the literature revealed no reports of a woman with Turner syndrome with aortic dissection at such a young age unless coarctation of the aorta was present. [23][24][25] Since she has the "affected" 3p haplotype associated with disease in the family, the early onset of her aortic disease may be due to inheriting two genetic conditions that predispose her to this disease. A second woman (III:32) with Turner syndrome in the family had both bicuspid aortic valve and coarctation of the aorta but did not have aortic dilation or dissection at the age of 43 years, consistent with her not inheriting the "affected" 3p haplotype.…”
Section: Discussionmentioning
confidence: 99%